PENGEMBANGAN BAHAN AJAR BERBASIS DISCOVERY LEARNING DENGAN KEARIFAN LOKAL UNTUK SISWA SMP/MTs - Mardia Hi Rahman; Saiful Latif; Ade Haerullah (EDUKASI, 2021)
The development research done at MTs Negeri 2 Halmahera Utara aims to: (1) produce physics teaching materials based on local wisdom in the Energy material for MTs class VII students, and (2) determine the feasibility of physics teaching materials based on local wisdom Energy materials for MTs students in class VII. This development research refers to the 4 steps of the 4-D model development design proposed by Thiagarajan, namely the stages of defining, designing, developing, and disseminating. The product trial consisted of validation by material experts, media experts, linguists, science teachers, and 5 students of MTs Negeri 2 Halmahera Utara class VII. Collecting data using interview guidelines, expert validation sheets, and understanding test sheets of teaching materials. This research produces a product in the form of physics teaching materials based on local wisdom in the form of a printed book and is suitable for use with eligibility criteria including content eligibility of 94% very feasible category, presentation feasibility 90% very feasible category, graphic feasibility 88% very feasible category, feasibility linguistics of 88% in the very appropriate category, and the average comprehension test of teaching materials of 90.5 in the high category.